2021
DOI: 10.1111/ijfs.15334
|View full text |Cite
|
Sign up to set email alerts
|

Microbial exopolysaccharides: role in functional food engineering and gut‐health management

Abstract: The objective of this review was to evaluate the structural and functional role of Microbial exopolysaccharides (EPS) in food products. EPS are biologically produced natural macromolecules that provides distinctive rheological and physicochemical properties to food matrix. Understanding the interactions of EPS with food components at the molecular level enables the application in bakery products, dairy/non-dairybased functional products, processed meat, as probiotics delivery vehicles, etc. Further information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
0
6
0
3
Order By: Relevance
“…Polysaccharides of microbial origin have been known not only to affect the GM structure and function, but have shown an overall improvement in gut health ( 75 ). Bacterial EPSs can modulate the host-bacterial interactions directly through the adhesion of bacteria to gut epithelium, modulation of host immunity, and the function of GM ( 133 , 134 ). EPSs secreted by certain gut bacteria can further be metabolized by some other commensal microbes ( Figure 1 ).…”
Section: Prebiotic Properties Of Microbial Polysaccharidesmentioning
confidence: 99%
“…Polysaccharides of microbial origin have been known not only to affect the GM structure and function, but have shown an overall improvement in gut health ( 75 ). Bacterial EPSs can modulate the host-bacterial interactions directly through the adhesion of bacteria to gut epithelium, modulation of host immunity, and the function of GM ( 133 , 134 ). EPSs secreted by certain gut bacteria can further be metabolized by some other commensal microbes ( Figure 1 ).…”
Section: Prebiotic Properties Of Microbial Polysaccharidesmentioning
confidence: 99%
“…EPS mikroorganizmanın hücre içinde olabileceği gibi hücre dışına sentezlediği maddeler olup bazıları da hücre duvarı yapısında yer alan uzun zincirli homopolisakkarit veya heteropolisakkaritlerdir. EPS'ler probiyotikler tarafından üretilmekle birlikte prebiyotik etkileri sayesinde probiyotiklerin kolonizasyonunu da teşvik etmektedir (Muninathan, 2021). Maya hücre duvarında yer alan β-glukan da bir EPS'dir.…”
Section: Gelveri̇ Ekmeği̇ üReti̇mi̇nde Kullanilan Bi̇leşenlerunclassified
“…Probiotic bacteria cells are destroyed during freezing and aeration of the ice cream mixes and in storage; however, many researchers have shown that probiotic cultures have better viability in frozen products than in fermented milk [ 33 , 34 , 35 ]. The most commonly applied probiotic bacteria in food production, including ice cream, are Lactobacillus and Bifidobacterium [ 36 , 37 ]. The probiotic strains of these bacteria are potentially resistant to low temperatures during freezing, extremely low pH (1–4) in the stomach, the activity of digestive enzymes (bile salts and pancreatin) in the intestine, and toxic metabolites formed during digestion [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%